SEROPREVALENCIA DE Neosporacaninum EN BOVINOS LECHEROS DEL VALLE DE LIMA - Silva S, Pablo (2002)
The aim of the present study was to determine the seroprevalence of Neospora caninum in dairy cattle at the Lima Valley in year 2000. A total of 304 sera samples from dairy cows of 19 herds located in the northern(12 herds)and southern(7) part of Lima were analysed to detect antibodies against N.caninum using the immunofluorescense indirect test.29.65.1% (90/304)of the animals showed antibodies at the 1:200 dilution. The prevalence in the northern area was 40.8±8.8%(49/120),whereas in the southern area was 22.3±6.0%(41/184). All farm had seropositives animals to N.caninum. The results confirm the presence of N.caninum in dairy herds of the Lima valley.